2018
DOI: 10.7150/jca.21460
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response and Toxicity After Pressurized IntraPeritoneal Aerosol Chemotherapy

Abstract: Background: Pressurized Intraperitoneal Aerosol Chemotherapy (PIPAC) is a novel mode of intraperitoneal (IP) drug delivery claiming high IP tissue concentrations with low systemic uptake. The aim was to study inflammatory response and systemic toxicity after PIPAC.Methods: Retrospective monocentric analysis of a consecutive cohort of PIPAC patients between January 2015 and April 2016. Detailed hematological and biochemical analysis was performed the day before surgery and once daily until discharge. Comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Overall, the search identified: 23 stage 0 studies; 18 stage 1 studies and two protocol papers for stage 1 studies; 25 stage 2a studies, one protocol paper and five trial registrations (NCT01854255, NCT02735928, NCT03246321, NCT02604784 and NCT03124394) for stage 2a studies; six stage 2b studies and three protocol papers for stage 2b studies; and three protocol papers for stage 3 studies. Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the search identified: 23 stage 0 studies; 18 stage 1 studies and two protocol papers for stage 1 studies; 25 stage 2a studies, one protocol paper and five trial registrations (NCT01854255, NCT02735928, NCT03246321, NCT02604784 and NCT03124394) for stage 2a studies; six stage 2b studies and three protocol papers for stage 2b studies; and three protocol papers for stage 3 studies. Fig .…”
Section: Resultsmentioning
confidence: 99%
“…The chemotherapy regimens currently proposed are oxaliplatin alone for colorectal cancer and doxorubicin and cisplatin for PCs of other origins. Platinum agents may induce anaphylactic reactions and can irritate the eyes, skin and airways; they are toxic to the kidneys and bone marrow ( 14 , 15 ). Doxorubicin provokes mucosal inflammation, leukopenia and dilated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the vast majority of these studies reported outcomes of entire cohorts that received repetitive PIPAC with various drugs for PM of various origins without presenting subgroup analyses of patients who received PIPAC-OX for colorectal PM 27–34. Only two studies reported separate outcomes of repetitive PIPAC-OX for colorectal PM 35 36. By using a prospectively maintained database, Teixeira Farinha et al retrospectively included 20 patients with isolated colorectal PM who received 37 procedures 35.…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies reported separate outcomes of repetitive PIPAC-OX for colorectal PM 35 36. By using a prospectively maintained database, Teixeira Farinha et al retrospectively included 20 patients with isolated colorectal PM who received 37 procedures 35. They concluded that repetitive PIPAC-OX causes a modest and transitory inflammatory response without haematological, renal or hepatic toxicity 35.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation